2016
DOI: 10.1128/msystems.00051-16
|View full text |Cite
|
Sign up to set email alerts
|

A Simple Screening Approach To Prioritize Genes for Functional Analysis Identifies a Role for Interferon Regulatory Factor 7 in the Control of Respiratory Syncytial Virus Disease

Abstract: Making the most of “big data” is one of the core challenges of current biology. There is a large array of heterogeneous data sets of host gene responses to infection, but these data sets do not inform us about gene function and require specialized skill sets and training for their utilization. Here we describe an approach that combines and simplifies these data sets, distilling this information into a single list of genes commonly upregulated in response to infection with RSV as a model pathogen. Many of the g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
26
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(31 citation statements)
references
References 55 publications
(61 reference statements)
5
26
0
Order By: Relevance
“…Our data showing an antiviral role for IFI44 and IFI44L matches our previous study using a lentivirus screen (8) and a broader screen by another group using the same lentivirus panel (14). However, the data presented here is somewhat at odds with recently published studies investigating the impact of IFI44 (42) and IFI44L (43) on virus in vitro.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…Our data showing an antiviral role for IFI44 and IFI44L matches our previous study using a lentivirus screen (8) and a broader screen by another group using the same lentivirus panel (14). However, the data presented here is somewhat at odds with recently published studies investigating the impact of IFI44 (42) and IFI44L (43) on virus in vitro.…”
Section: Discussionsupporting
confidence: 90%
“…Our in vitro studies have some limitations, primarily the use of clonal cell lines to assay infection and proliferation. We note that transduction of polyclonal parental A549 cells with IFI44 is capable of restricting RSV infection similarly to the stably transduced cells, and that previous studies have observed similar impacts of IFI44 on proliferation (13, 18) or restriction of RSV (8). However, it is possible that clone-specific differences have some impact on either RSV infection or cell viability and these data should be interpreted with this limitation in mind.…”
Section: Discussionsupporting
confidence: 71%
See 2 more Smart Citations
“…Up-regulation of CLRs activates antiviral immune responses such as antigen processing and presentation, T cell activation and phagocytosis, suppressing viral dissemination within the host. Nevertheless, CLRs can be a double-edged sword as some viruses have evolved to use these receptors for viral entry into host cells, avoiding immune recognition, where kidnapping the host cell machinery they produce hundreds of new copies of themselves spreading their copies further into the host [54].…”
Section: Discussionmentioning
confidence: 99%